2012
DOI: 10.2109/jcersj2.120.494
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of spindle and square bipyramid-shaped anatase-type titanium dioxide crystals by a solvothermal method using ethylenediamine

Abstract: Morphological control as well as formation of nanoparticles of anatase-type titanium dioxide has been achieved by a solvothermal treatment of a water-soluble citratoperoxotitanium (CPT) complex using ethylenediamine (EDA) as a key solvent in the presence of a given amount of water. When the EDA concentration in the whole solvent (EDA + H 2 O) remained low less than 12 M, the powder obtained after the solvothermal treatment consisted of spindle-like anatase particles. With an increase of the EDA concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…7(b)). A SAED pattern of a spindle-shaped particle revealed that the major axis was parallel to the c-axis [71]. By increasing the en concentration in the solvent, the shape of the particles changed from spindle to square bipyramid (Fig.…”
Section: Morphological Control Of Anatase-type Titania Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…7(b)). A SAED pattern of a spindle-shaped particle revealed that the major axis was parallel to the c-axis [71]. By increasing the en concentration in the solvent, the shape of the particles changed from spindle to square bipyramid (Fig.…”
Section: Morphological Control Of Anatase-type Titania Nanocrystalsmentioning
confidence: 99%
“…These results indicate that the morphology of anatase particles can be modified from a nanoparticle to spindleshaped by adjusting the concentration of en used in the solvothermal system using the en/H2O solution of the titanium-citrato complex. When the titanium-glycolato complex, or TiOCl2 (which can be prepared from TiCl4 and ice water) was used as initial titanium source, anatase particles with a similar shape could be obtained by carefully choosing the synthetic conditions [71]. Using a mixed en/H2O solvent, sheet-like titanic acid was produced in an intermediate phase, regardless of the en concentration.…”
Section: Morphological Control Of Anatase-type Titania Nanocrystalsmentioning
confidence: 99%
“…To date, we have succeeded in synthesizing titania with controlled structures and morphologies using a hydrothermal treatment of a series of water-soluble titanium complexes employing additives [10][11][12][13]. During this research, we found that anisotropically grown rutile titania nanocrystals along the c-axis is as formed by the hydrothermal treatment of a glycolato-titanium complex using glycolic acid, which is the simplest ␣-hydroxy acid (R(OH)COOH), as a morphological control agent, and the aspect ratio increases with an increase in the quantity of glycolic acid added [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, spindle-and square bipyramidal-shaped anatase was synthesized using high concentrations of an amine, such as ethylenediamine, even though only the single phase of brookite was formed using low concentrations of amine. 37) Note that solvothermal treatment of titanium complexes in rather concentrated amine solutions (e.g., more than 12 M of ethylenediamine) leads to the formation of spherical mesoporous agglomerations composed of tiny particles of 38) The formation of spheres might be explained by DLVO theory. On the other hand, using 1,3-diaminopropane, multi-pronged needles of anatase crystals were obtained, as shown in Fig.…”
Section: Titania Crystals With Various Morphologiesmentioning
confidence: 99%